First 100 Dobutamine Stress Echocardiography in Medicare National Hospital, Nepal - Upadhyaya, Abani B; Shrestha, Denis (Nepalese Heart Journal, 2004)
In patients with known or suspected CAD, diagnosis and risk stratification can be aided by non-invasive tests for myocardial ischemia. The scientific use of stress echo, started twenty years ago and for at least a decade, it has been considered a method of established usefulness. Medicare National Hospital, Kathmandu introduced stress echo, in June 2003 and has performed over 140 stress echo. so far, out of which 130 are dobutamine stress echo. The data of first 100-dobutamine-stress echo. were analyzed and presented.